Holocene reconfiguration and readvance of the East Antarctic Ice Sheet - Sarah L. Greenwood (Nature Portfolio, 2018)
Ice sheets are vulnerable to changes in the environment where ice discharges into the ocean. Here, the authors show that, in spite of widespread retreat following the last glacial maximum, a sub-sector of the East Antarctic Ice Sheet in the Ross Sea underwent sustained readvance.